Domestic transfer pricing adjustments: A zero-sum-game of state tax revenue? A tax supervision case study in the tax office - Fajar Surya Putra; Yeni Farida (Directorate General of Taxes, 2024)
According to some experts, domestic transfer pricing correction is believed not to impact the national tax revenue. This is based on the assumption that any increase in tax revenue resulting from the correction at one tax office will be offset by a decrease of the same amount at another tax office (zero-sum-game). This research uses a qualitative method by using a case study approach to describe the impact of domestic transfer pricing correction on national tax revenue. All case studies happened at the Jakarta Gambir Two Tax Office from January to October 2022. This tax office was chosen because the researcher can participate in the tax supervision process. As a consequence, the researcher can gain a better understanding of the case studies. The results show that intra-group service corrections materially impact the national tax revenue, while domestic loan corrections only have a small impact.